PENGEMBANGAN WISATA DESA SEBAGAI STRATEGI PENGENTASAN DESA TERTINGGAL: DESA GAJAHREJO, KABUPATEN MALANG - Zihla Hasnatul Layli; Maryunani Maryunani; Wildan Syafitri (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2020)
Regional potential and economic level are closely related. The abundance of natural resources will support rapid economic growth. However, in reality, there are still many areas that have abundant natural resources potential but the economic level is low and even classified as an underdeveloped village, such as Gajahrejo Village – Genangan District, Malang Regency. The purpose of this study was to identify the characteristics of village and to formulate poverty alleviation strategies in Gajahrejo Village by using the Sustainable Livelihood Approach (SLA). The study used Partial Least Square (PLS) analysis. The study showed that, based on SLA and in accordance with the characteristics of Gajahrejo Village the best indicator for shaping human capital was skills, natural capital was tourism potential, financial capital was asset owned, social capital was organization, and physical capital was transportation. Based on the path diagram, the dominant variable in shaping SLA was natural capital, and the most dominant indicators in measuring the construction of natural capital was tourism potential. The poverty alleviation strategy for the Gajahrejo Village which consists of 4 hamlets as a tourist village is by developing the role of each hamlet in according respecting to each characters, for instance, Krajan hamlet as a tourism market, Sumber Lele hamlet as an education tourism, Ardimulyo hamlet as a natural tourism, and Bajulmati hamlet as a beach tourism.